(3eHGOF GdeMGSHI GdeGdjI (B/s - (3fhQ, CMeO eMehOs ((3GdGScfOQjI(B: s (3GdOGQ GdLGeYjI(B, s, 2003)
.(3aj JYQja GdeMGSHI hJMOjO CgOGagG hhXGFagG hGWGQgG GdacQj eY QHWgG HeYGjjQ GdeMGSHI GdeUQjI hGdOhdjI, aj GdJSLjd GdeMGSHj dYedjGJ GdeTQhY hGSJceGd GdOhQI GdeMGSHjI eY QHWgG HeYGjjQ GdeMGSHI GdeUQjI hGdOhdjI, aj GdeYGdLI GdeMGSHjI ddYedjGJ GdjhejI ddeTQhY eY QHWgG HeYGjjQ GdeMGSHI GdeUQjI hGdOhdjI, GSJceGd GdOhQI GdeMGSHjI hGYOGO GdbhGFe GdeGdjI aj GdefTBJ GdJLGQjI hGdUfGYjI eY QHWgG HeYGjjQ GdeMGSHI GdeUQjI hGdOhdjI, GdeTGcd GdeMGSHjI GdeJYdbI HGdJMbb ef GdCUhd hGdNUhe hGdGaUGM YfgG eY QHWgG HeYGjjQ GdeMGSHI GdeUQjI hGdOhdjIs
Keywords: (3GdGOGQI GdeGdjIs; (3GdeMGSHIs